The development of candy bar from garbanzos - Aujero, Ma. Gerlia Cordero (1995.)
As an economically affordable candy bar from dried garbanzos seeds was developed as ready to eat food item to supplement the daily protein requirement of the local consumers.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Candy bar; Garbanzos